Paper art II - Wang, Anlei; Xia, Jiajia (Shenzhen, China Artpower International Publishing Co., Ltd., 2015)
"What is paper art? The crease and fold paper creates incredible paper installation art etc. This book offers readers a comprehensive introduction of the current paper art design, especially in recent two years. As a book specializing in present paper art design, it collects plenty of works from excellent design teams. This book is divided into three parts: graphic paper art, 3D paper art, and interior paper art. In a word, this book will leave you a deep impression at first sight. It is a path that leads to greatness and success."
Keywords: Paper art -- 21st century -- Pictorial works; Paper art